A new species of Amphictene (Annelida, Pectinariidae) from the Gulf of Mexico, with a redescription of Amphictene guatemalensis (Nilsson, 1928) - García Garza, María Elena; León González, Jesús Angel de (2014)
The genus Amphictene is reported for the first time from Mexico. Previous records for America are restricted to Brazil (A. catharinensis) (Grube, 1870), and Guatemala (A. guatemalensis) (Nilsson, 1928). In this paper we describe a new species, Amphictene helenae sp. n., characterized by the presence of three pairs of tentacular cirri, while other species have only two pairs. The new species is closely similar to Amphictene catharinensis, and can be distinguished by the presence of a circular group of glandular papillae inserted between the lines of glandular cirri present from the second segment. A. guatemalensis is redescribed based on type material; it differs from the new species in the presence of two pairs of tentacular cirri on segments 1 and 2, six pairs of glandular cirri on the third segment, and four glandular lobes fused in pairs on the fourth segment.